Boosting Chemoselective Hydrogenation of Nitroaromatic via Synergy of Hydrogen Spillover and Preferential Adsorption on Magnetically Recoverable Pt@Fe2O3. Issue 11 (20th January 2023) - Yue, Guichu; Yu, Yu; Li, Shuai; Li, Huaike; Gao, Songwei; Wang, Yaqiong; Guo, Wei; Wang, Nü; Li, Xiuling; Cui, Zhimin; Cao, Changyan; Jiang, Lei; et al.
Abstract: It is highly desired but challenging to design high performance catalyst for selective hydrogenation of nitro compounds into amino compounds. Herein, a boosting chemoselective hydrogenation strategy on Pt@Fe2 O3 is proposed with gradient oxygen vacancy by synergy of hydrogen spillover and preferential adsorption. Experimental and theoretical investigations reveal that the nitro is preferentially adsorbed onto oxygen vacancy of Pt@Fe2 O3, meanwhile, the H2 dissociated on Pt nanoparticles and then spillover to approach the nitro for selective hydrogenation (>99% conversion of 4‐nitrostyrene, > 99% selectivity of 4‐aminostyrene, TOF of 2351 h −1 ). Moreover, the iron oxide support endows the catalyst magnetic retrievability. This high activity, selectivity, and easy recovery strategy provide a promising avenue for selective hydrogenation catalysis of various nitroaromatic. Abstract : A magnetically separable Pt@Fe2 O3 can achieve high chemoselective hydrogenation of nitroaromatic via synergy of high efficient hydrogen spillover on Pt and preferential adsorption of nitro on oxygen vacancy in Fe2 O3 .